Serials collection management in recessionary times - Lawson, Karen (London New York : Routledge, 2011)
This book covers the implications for libraries of a broad range of technological and economic challenges. These challenges include the fallout from the global economic crisis, the positioning of usage statistics, the advent of open access scholarship, database management, responding to budgetary constrictions and general access to serials. Taken as a whole, this collection provides practitioners in the library sector and in higher education with a wide variety of insights on the strengths, weaknesses, threats and opportunities involved with serials collection management in recessionary times, written by academic librarians, vendors, publishers, fundraisers, and higher education professionals.
"This book is a reproduction of The Serials Librarian, vol. 59, issues 2, 3-4"--T.p. verso.
"This book was published as a special issue of The Serials Librarian"--half title.
Includes bibliographical references and index
Keywords: Acquisition of serial publications; Libraries and electronic publishing; Periodicals; Research libraries